Pilocytic Astrocytoma of the Cerebellopontine Angle with cerebrospinal fluid Spread in an Adult: A Case Report - Bıyıklı, Erhan; Kursun, Meltem; Oguzsoy, Tuba; Bozkurt, Suheyla; Bayraklı, Fatih (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Pilocytic astrocytoma of the cerebellopontine angle (CPA) is uncommon, and its spread to the cerebrospinal fluid (CSF) at the time of diagnosis has not been reported in the literature.Case Presentation We report the case of a 33-year-old man with multifocal pilocytic astrocytoma diagnosed by magnetic resonance imaging (MRI) and confirmed by histopathological examination, and present the radiological and histopathological findings.Conclusion In the case herein reported, we observed spread of the pilocytic astrocytoma of the CPA to the CSF at the initial diagnosis, and early detection by MRI is very important regarding the treatment modality and prognosis.
Keywords: cerebellopontine angle; pilocytic astrocytoma; vestibular schwannoma